2013
DOI: 10.1111/asj.12064
|View full text |Cite
|
Sign up to set email alerts
|

Rectal temperature as an indicator for heat tolerance in chickens

Abstract: High environmental temperature is perhaps the most important inhibiting factor to poultry production in hot regions. The objective of this study was to test adaptive responses of chickens to high ambient temperatures and identify suitable indicators for selection of heat-tolerant individuals. Full-sib or half-sib Anak-40 pullets (n = 55) with similar body weights were raised in a room with a temperature ranging from 24°C to 28°C, and relative humidity of 50% from 61 to 65 days of age. On day 66, the ambient te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 8 publications
3
13
0
1
Order By: Relevance
“…A previous study reported a significant correlation between BT and survival in chickens during heat stress [ 31 ], which suggested that selection for BT during heat stress has potential to reduce mortality. In our study, heritabilities were low (0.03–0.11) for BT and higher (0.10–0.11) for absolute BT than that previously estimated for a broiler line i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported a significant correlation between BT and survival in chickens during heat stress [ 31 ], which suggested that selection for BT during heat stress has potential to reduce mortality. In our study, heritabilities were low (0.03–0.11) for BT and higher (0.10–0.11) for absolute BT than that previously estimated for a broiler line i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, changes in t cloacal during heat stress are used to evaluate the degree of adaptation of broiler chickens to hot‐dry conditions (Chen et al. ), and level of reactive oxygen species (ROS) in broilers (Azad et al. ), generated in excess during heat stress (Lin et al.…”
Section: Introductionmentioning
confidence: 99%
“…It indicates the balance between heat loss and heat gain in broiler chickens (Edgar et al 2013). Thus, changes in CT during heat stress may be of value in determining the resistance of broiler chickens to hot-dry conditions (Chen et al 2013). Isidahomen et al (2012) reported that the normal upper limit of body temperature in poultry does not exceed 42.2°C.…”
Section: Introductionmentioning
confidence: 99%